A clinical and immunological study of phototoxic regimen of ultraviolet A for treatment of alopecia areata: a randomized controlled clinical trial. (18th August 2019) - El-Mofty, Medhat; Rasheed, Hoda; El-Eishy, Nermin; Hegazy, Rehab A.; Hafez, Vanessa; Shaker, Olfat; El-Samanoudy, Solwan I.
Abstract: Background: Various therapeutic agents have been described for alopecia areata but none is satisfactory. The use of ultraviolet A phototherapy in phototoxic regimens has emerged lately with promising results. Objective: To determine the efficacy and safety of phototoxic regimen of psoralen ultraviolet A (PUVA) in comparison to conventional therapy with intralesional corticosteroids in patients with alopecia areata. Methods: In this randomized controlled clinical trial, 40 patients were randomized to either phototoxic regimen of psoralen ultraviolet A group or potent intralesional corticosteroids group for three months. Study ended at six months. The primary outcome was treatment success: sustained regrowth of hair in ≥80% of the affected areas at six months. Tissue cytokines were assessed at zero and three months. Results: At six months, treatment success was achieved by 45% of patients, similarly in both groups. Tissue cytokine expression correlated well with clinical response. Conclusion: Phototoxic regimen of topical PUVA deserves a place among therapeutic tools used in management of alopecia areata especially in more extensive conditions where intralesional corticosteroids would not be suitable. Trial registration: https://clinicaltrials.gov/ct2/show/record/NCT01559584